Etiology and clinical spectrum of acute undifferentiated fever illness in patients in a tertiary care hospital Sheri Kashmir institute of medical science Soura, Jammu and Kashmir - Gazala, Sheenam; Chesti, Mohmad Saleem; Mushfiq, Syed (International Journal of Advances in Medicine, 2021)
Background: Current study aimed at s to delineate the etiology and clinical parameters associated with AUFI presenting to emergency department in a tertiary care hospital. Methods: This was a prospective hospital based study carried out at emergency medicine, SKIMS hospital, Soura Kashmir, India July 2017 to august 2018. Patients with acute undifferentiated fever were enrolled. Descriptive statistics were calculated in terms of mean±SD for continuous variables like age of the patients and duration of fever, Frequency and percentage were used to analyse categorical variables such as causes of fever and gender, while as descriptive analysis was calculated in terms of mean±SD for continuous variables like age of the patients and duration of fever. Results: Total numbers of patients included were 174, among these 112 (64.3%) were males and 62 (35.6%) were females. Most patients were diagnosed enteric fever (N=59, 33.9%) followed by UTI (N=25, 14.3%) dengue (N=12, 6.8%) and malaria (N=8, 4.5%) while rest of cases were associated with other viral illnesses (N=70, 40.5%) based on clinical basis and inconclusive laboratory results. Conclusions: Enteric fever was found to be the most common cause of acute undifferentiated fever followed by dengue and other viral illnesses, although causes and clinic spectrum of AUFI is varied.